2019
DOI: 10.1172/jci.insight.130056
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of leukotrienes by senescent lung fibroblasts promotes pulmonary fibrosis

Abstract: Conflict of interest: CDW, AR, and JC are inventors on a patent application (no. WO2019070407) for eicosanoids as biomarkers of senescence. AV is currently an employee at UNITY Biotechnology. HAC is the scientific founder of Pliant Therapeutics, which develops antifibrotic drugs and owns equity in the company. JC is the scientific founder of UNITY Biotechnology, which develops senolytic and other drugs to combat aging, owns equity in the company, and receives research funding from the company. JC is also named… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 55 publications
(77 reference statements)
1
65
0
Order By: Relevance
“…Accumulation of senescent cells in the fibrotic tissue has been linked to the severity of IPF, and earlier studies have shown that modulation of 5-LO and COX-2 in senescent fibroblasts [93,94]. In vitro, induction of senescence in human lung fibroblasts (IMR-90) using irradiation increased expression of phospho-5-LO/total 5-LO ratio and secretion of cysLTs [95]. Further, the cysLT-rich conditional medium of senescent IMR-90 fibroblasts induced pro-fibrotic signaling in naïve fibroblasts, which was abrogated by inhibition of 5-LO.…”
Section: Cellular Senescence and Leukotriene Metabolism In Pulmonary mentioning
confidence: 99%
“…Accumulation of senescent cells in the fibrotic tissue has been linked to the severity of IPF, and earlier studies have shown that modulation of 5-LO and COX-2 in senescent fibroblasts [93,94]. In vitro, induction of senescence in human lung fibroblasts (IMR-90) using irradiation increased expression of phospho-5-LO/total 5-LO ratio and secretion of cysLTs [95]. Further, the cysLT-rich conditional medium of senescent IMR-90 fibroblasts induced pro-fibrotic signaling in naïve fibroblasts, which was abrogated by inhibition of 5-LO.…”
Section: Cellular Senescence and Leukotriene Metabolism In Pulmonary mentioning
confidence: 99%
“…The expression of p16 INK4a in macrophages can suppress M1 polarization and hence the secretion of inflammatory factors by these cells [61]. On the other hand, the SASP secreted by senescent thyroid cells skews macrophage polarization to M2 caused by prostaglandin E2 [62], a prominent SASP factor [63].…”
Section: Interaction Of Senescent Cells With Macrophagesmentioning
confidence: 99%
“…We reported the presence of cellular senescence markers, such as p21, p53, γ-H2AX and SA-βgal staining, which along with the expression of SASP components represent a source of chronic profibrotic signaling through the activation of Il-6, Mcp1, TNF-α, and IL-1α. The presence of this secretory phenotype has already been confirmed in AE2 cells and lung fibroblasts of IPF patients (2,54). We previously demonstrated that chronic activation of the mTOR/PGC-1β pathway induces lung epithelial cells into a senescence phenotype, possibly due to augmented ROS-induced molecular damage (51).…”
Section: Discussionmentioning
confidence: 68%
“…Growing evidence indicates that aging and cellular senescence are tightly interrelated to mitochondrial dysfunction (16,54). Accumulation of dysmorphic/dysfunctional mitochondria has been described in several aged tissues, including AE2 cells of IPF lungs.…”
Section: Discussionmentioning
confidence: 99%